PENGEMBANGAN MEDIA KARTU KUARTET UNTUK PENGENALAN KARIR PESERTA DIDIK DI SEKOLAH DASAR - Krispaty, Yasa Galuh Krispaty; Soesilo, Tritjahjo Danny Soesilo; Septiningtyas, Maya Rahardian Septiningtyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Career introduction is an essential first step in the career planning process for students. This study aims to develop an engaging and user-friendly quartet card game as a career introduction tool for elementary school students. The research follows the Research and Development (R&D) methodology. The study resulted in a career card game designed to introduce career concepts to elementary students. The media expert evaluation scored the game 100, categorizing it as 'excellent,' while the material expert evaluation scored 84, categorizing it as 'good.' Additionally, limited trials showed that before the intervention, 28.18% of students had a 'low' level of career introduction, whereas after the intervention, 95.46% reached a 'very high' level. Based on these findings, the career card game is concluded to be an effective tool for supporting career introduction in elementary schools.